Extreme loads analysis of a site-specific semi-submersible type wind turbine. (30th December 2020) - Xu, Xiaosen; Gaidai, Oleg; Naess, Arvid; Sahoo, Prasanta
ABSTRACT: As a vital key part of the modern offshore wind energy industry, floating offshore wind turbines (FOWT) are built to generate green renewable energy. Robust prediction of extreme loads during FOWT operation is an important safety concern. In this paper, the FAST code has been used to analyse offshore wind turbine internal bending moments due to environmental hydrodynamic wave loads, acting on a specific FOWT under actual local sea conditions. This paper advocates a computationally efficient Monte Carlo based methodology for estimating extreme load or response statistics, based on simulations or measurements. For this purpose, the averaged conditional exceedance rate (ACER) method is proposed. The described approach may be well used at the design stage, while defining optimal wind turbine parameters that would minimise potential FOWT mechanical damage due to excessive environmental loadings.